The Relationship between Decision Making Style of Principals of Senior Secondary Schools and their Teaching Experiences: The impact of decision making style on teaching experiences of principals in senior secondary schools (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The main aim of the exploration present in this paper is to study the relation of the decision making style of principals of senior secondary schools with their teaching experiences. For this, the researcher has randomly chosen blocks from six districts of the Kumaon Mandal of Uttarakhand. The study has done on the seventy six principals of senior secondary schools of different categories from these blocks. The samples of these principals have drawn through a stratified random sampling technique. The Decision making style scale created by Ganihar (2005) is used to gather information from sample subjects. Investigations of gathered information or data score are finished with the help of Pearson Chi-Square correlation coefficients and Contingency Coefficients determined by utilizing SPSS programming. The investigation revealed that the routine decision-making style of principals of senior secondary schools is highly associated with their teaching experiences, but compromise and heuristic decision-making styles are negligibly associated with their teaching experiences.